Spatio-temporal analysis of decadal-scale patterns in barrier island response to storms: Perdido Key, NW Florida. (4th March 2018) - Sankar, Ravi D.; Donoghue, Joseph F.; Kish, Stephen A.
Abstract: The ability to accurately quantify shoreline variability is essential in order to establish aggressive mitigation strategies, based on recent global climate change projections. This investigation employed a suite of coastal data (topographic maps, aerial photography, satellite imagery and lidar) to establish decadal trends of shoreline movement along Perdido Key, a sandy barrier island off Florida's northwest coast. The technique used to detect morphologic change with time was a recently developed tool, Analyzing Moving Boundaries Using R. This innovative methodology improves our understanding of the evolution of coastal systems by modeling shoreline variance using a method that is sensitive to shoreline shape. Results show that the barrier shoreline is a highly dynamic feature with distinct zones of erosion and accretion that are pervasive over time. In general, the island is displaying a mechanism of rotational instability with the eastern half retreating, and the western portion advancing. The inflection point, around which this rotational shifting is taking place, lies at the center of a Pleistocene headland located along the island's midpoint. The results of this study suggest that coastal evolution along the island may be meta-stable, with trends in shoreline variance corresponding mainly to discrete storm events in time.